Beyond Indulgences Luther's Reform of Late Medieval Piety, 1518-1520 - Johnson, Anna Marie (Early Modern Studies, 2021)
Between Luther's Ninety-Five Theses in 1517 and his excommunication from the church in 1520, he issued twenty-five sermons and treatises on Christian piety, most of them in German. These pastoral writings extended his criticisms of the church beyond indulgences to the practices of confession, prayer, clerical celibacy, the sacraments, suffering, and death. These were the issues that mattered most to Luther because they affected the faith of believers and the health of society. Luther's conflict with Rome forced him to address the issue of papal authority, but on his own time, he focused on encouraging lay Christians to embrace a simpler, self-sacrificing faith. In these pastoral writings, he criticized theologians and church officials for leading people astray with a reliance on religious works, and he began to lay the foundation for a reformed Christian piety